Comparison of general anesthesia and continuous intravenous sedation for electrochemotherapy of head and neck skin lesions - Benedik, Janez; Ogorevc, Barbara; Brezar, Simona Kranjc; Cemazar, Maja; Sersa, Gregor; Groselj, Ales (Frontiers in Oncology, 2022)
Background. Electrochemotherapy of cutaneous tumor nodules requires local or general anesthesia. For multiple and larger nodules, general anesthesia is recommended by standard operating procedures. The choice of general anesthesia is at the discretion of the treating center. Continuous intravenous sedation is also an option. Our study aimed to elucidate the tolerability, safety and possible advantages of continuous intravenous sedation in comparison to general anesthesia in patients undergoing electrochemotherapy. Patients and Methods. In the prospective study, 27 patients undergoing electrochemotherapy were either under general anesthesia or under continuous intravenous sedation. Evaluated were different endpoints, such as feasibility and safety, duration of anesthesia and compliance with the patients. Results. Ten patients were treated under general anesthesia, and 17 patients were under continuous intravenous sedation. The comparison of the approaches indicated that continuous intravenous sedation required a lower overall dosage of propofol, a shorter duration of anesthesia, a shorter time to reach an Aldrete score >8, and greater satisfaction of the patients with the procedure compared to general anesthesia. Conclusion. The results indicate the feasibility and safety of continuous intravenous sedation for patients undergoing electrochemotherapy of cutaneous tumor nodules. This proved the preferred choice of anesthesia due to its shorter duration and better compliance with the patients compared to general anesthesia.